Fictitious price falls and the buying activity of retail investors - Mourad Junior, Ahmad Abdallah (2019)
This work shows that retail investors respond positively to stock prices\' drops in itself, that is, price drops that do not reflect any relevant information about that particular stock. To do so, I use TAQ data between 2010 and 2017 and identify retail trades using a recent innovation proposed by Boehmer, Jones e Zhang (2017). I explore two distinct events that produce immaterial price drops on stock prices. The first one is the mechanical price drop of a stock during its ex-dividend date: I document that retailers increase their buying activity of a stock during its ex-dividend date, regardless of the fact that this price drop is meaningless and is just an adjustment to the next cash dividend payout that its new shareholders are not entitled to receive. This result is consistent for different specifications; also, when I take into account the selling activity of retailers, I find that the net buying activity also respond positively to these price drops. The second exercise consists in evaluating if individuals display left-digit bias when they purchase stocks: indeed, when the price of a stock fluctuates around an integer number, individuals focus their purchases on trade prices just below that integer number, in spite of the fact that the difference between the trade price and its next integer number is meaningless in relative terms. I also find that individuals display left-digit bias for different nominal stock prices. Both exercises suggest that individuals neglect the informational role of stock prices, as they react positively to price falls that are non-material.